Preparing STEM Teachers for Integration of NGSS: A Summer Workshop Development - Gonca Altuger-Genc; Marjaneh Issapour (Journal of Education and Learning (EduLearn), 2015)
The increasing emphasis on Science, Technology, Engineering and Mathematics (STEM) education in United States and across the world created the demand for STEM education to start as early as elementary school. Especially in the past decade, the demand for middle schools and high schools to increase the involvement of the STEM components in their curriculum has been on the rise.  The Next Generation Science Standards (NGSS)(http://www.nextgenscience.org/) are testimonial to this demand and need.  With the fast-pace the NGSS are being adopted by different states, the expectations from science, engineering, and technology teachers to develop and design their courses to reflect the new standards and meet the updated goals increased.  To support teachers with the necessary resources and training, a Summer STEM training program and a set of STEM training modules have been developed by a 4-year accredited State College.   This paper provides an overview of the STEM initiatives and a step-by-step approach of the design and development of the STEM modules to train K-12 teachers.